Coastal Tourism Management Model toward Developing Independent Tourist Village in Central Lombok District, Indonesia - Mustajab Hakim; Abdul Hakim; Luchman Hakim; Nuddin Harahab (Resources, 2018)
Village development aims to improve the welfare of villagers and the quality of human life. The purpose of this study was to formulate a coastal tourism management model toward developing independent tourist villages. This study employed a quantitative approach by using survey methods. The data analysis was performed using structural equation modeling (SEM). There were four variables namely: the potential of mangrove ecosystem, the perception of the coastal community, the coastal tourism facilities, and the coastal ecotourism. The results indicated that there were two variables which had a significant effect on the management of coastal tourist villages, namely the perception of coastal community and coastal ecotourism. Furthermore, the management of a coastal tourist village had a significant effect on the development of independent coastal tourist villages, and the management of coastal tourist villages was a strong mediator to develop an independent coastal tourist village.